2012
DOI: 10.1186/1759-2208-3-4
|View full text |Cite
|
Sign up to set email alerts
|

Pathway control in the self-construction of complex precipitation forms in a Cu(II)-oxalate system

Abstract: Text AbstractBackground: Many biological systems contain complex precipitation patterns. These structures are considered to be the result of finely tuned and genetically encoded developmental pathways. The amount of encoded information needed to generate and manipulate these structures is poorly understood. Investigating the dynamics of spontaneous pattern formation in non-biological systems provides insights to the physio-chemical phenomena that biological systems must have harnessed for living systems and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…Although the characterisation of such crystals does not fall into the scope of this study, we note that those were identified as Na 2 Cu(C 2 O 4 ) 2 Á2H 2 O in a similar system. 26 To see whether a pattern different from the annular one can be achieved in the case of the chosen transition metals when dissolution is excluded, reverse injection experiments were also performed. In these situations, the solution of the transition metal ions was pumped into the host oxalate solution; the patterns observed at Q = 1 mL min À1 flow rate are presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although the characterisation of such crystals does not fall into the scope of this study, we note that those were identified as Na 2 Cu(C 2 O 4 ) 2 Á2H 2 O in a similar system. 26 To see whether a pattern different from the annular one can be achieved in the case of the chosen transition metals when dissolution is excluded, reverse injection experiments were also performed. In these situations, the solution of the transition metal ions was pumped into the host oxalate solution; the patterns observed at Q = 1 mL min À1 flow rate are presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…10,11 Gravity current plays an important role in the emergence of a copper oxalate precipitate pattern characterized by radial lines along which precipitate sedimentation occurs. 12,13 As the dense solution containing copper ions is pumped into the sodium oxalate solution through an inlet, it spreads on the bottom of the dish. The circular symmetry of the precipitate will, however, be broken since the tip of the gravity current is hydrodynamically unstable.…”
mentioning
confidence: 99%